Giải pháp đẩy mạnh xuất khẩu mặt hàng quế khu vực các tỉnh phía Bắc - Nguyễn, Đình Bàn (2011)
Tác giả: Nguyễn Đình Bàn, CN; Cù Đức Đua, CN; Lê Đình Nhiên, CN; Nguyễn Mạnh Cường, KS; Trần Văn Quang, CN -- Từ khóa: Quế; Xuất khẩu